PH-shifting formation of goat milk casein nanoparticles from insoluble peptide aggregates and encapsulation of curcumin for enhanced dispersibility and bioactivity. (15th January 2022) - Du, Xiaojing; Jing, Huijuan; Wang, Li; Huang, Xin; Mo, Ling; Bai, Xinpeng; Wang, Hongxin
Abstract: The insoluble peptide aggregates formed by proteolysis are usually discarded by food industries, which results in significant wastage of resources and burden on the related industries. In the present study, insoluble peptide aggregates formed during enzymatic hydrolysis of goat milk casein protein (GCA) were used to prepare goat milk casein nanoparticles (GCP) using a controlled pH-shifting treatment. Next, hydrophobic curcumin (Cur) was embedded in the GCP core, and nano-scale stable hydrophilic particles (GCP-Cur) were successfully prepared. The XRD and FT-TR spectroscopy results showed that the Cur was successfully encapsulated in GCP nanoparticles in an amorphous form, and Cur loading does not cause conformational changes. The morphological results also verified the successful design of the GCP-Cur nanoparticles. Furthermore, the GCP-Cur nanoparticles significantly improved the water solubility, storage stability, in vitro bioaccessibility, and antioxidant activity of Cur. Moreover, the anti-gastric digestion properties of GCP-Cur nanoparticles could control the effective release of Cur from the composite particles into the intestine, and can thus be used as a potential delivery carrier for biologically activity. This research provides theoretical and technical guidance for the development and high-value application of these low-value peptide byproducts. Highlights: pH-shifting processes of insoluble goat milk casein aggregates (GCA) were studied. pH- shifting formation of goat milk casein nanoparticles (GCP) from GCA. GCP exhibited good thermal storage stability and smaller average particle size. Curcumin (Cur) was successfully loaded in GCP by controlled pH-shifting processes. The antioxidant activity, solubility and stability of Cur were improved.